Conformation changes in human hair keratin observed using confocal Raman spectroscopy after active ingredient application - Essendoubi, M.; Meunier, M.; Scandolera, A.; Gobinet, C.; Manfait, M.; Lambert, C.; Auriol, D.; Reynaud, R.; Piot, O. (International journal of cosmetic science, 2019)
Objective In hair care cosmetic products’ evaluation, one commonly used method is to evaluate the hair appearance as a gold standard in order to determine the effect of an active ingredient on the final state of the hair via visual appreciation. Although other techniques have been proposed for a direct analysis of the hair fibres, they give only surface or structural information, without any accurate molecular information. A different approach based on confocal Raman spectroscopy has been proposed for tracking in situ the molecular change in the keratin directly in the human hair fibres. It presents a high molecular specificity to detect chemical interactions between molecules and can provide molecular information at various depths at the cortex and cuticle levels. Methods To evaluate the potential of confocal Raman spectroscopy in testing the efficiency of cosmetic ingredients on keratin structure, we undertook a pilot study on the effectiveness of a smoothing shampoo on natural human hair, by analysing α‐helix and β‐sheet spectral markers in the Amide I band and spectral markers specific to the cystin sulfur content. Results We confirmed that an active proved to be effective on a gold standard decreases α‐helix keratin conformation and promotes β‐sheet keratin conformation in the hair fibres. We also showed that treatment with the effective active decreases the intensity of covalent disulfide (S–S at 510 cm‐1) cross‐linking bands of cysteine. These data confirm that the effective active also acts on the tertiary structure of keratin. Conclusion From these experiments, we concluded that the effective active has a smoothing effect on the human hair fibres by acting on α‐helix and β‐sheet keratin conformation and on the tertiary structure of keratin. Based on these results, confocal Raman spectroscopy can be considered a powerful technique for investigating the influence of hair cosmetic ingredients on keratin structure in human hair fibres. Moreover, this analytical technique has the advantage of being non‐destructive and label free; in addition, it does not require sample extraction or purification and it can be applied routinely in cosmetic laboratories. Résumé OBJECTIF Dans l’évaluation des produits cosmétiques pour le soin des cheveux, une méthode communément utilisée consiste à évaluer l'aspect des cheveux afin de déterminer l'effet d'un principe actif sur l’état final des cheveux via l'appréciation visuelle. Bien que d'autres techniques ont été proposées pour une analyse directe de la fibre capillaire, elles ne donnent que des informations de surface ou de structure, sans aucune information moléculaire précise. Une approche différente par la spectroscopie confocale Raman a été proposée pour le suivi in situ du changement moléculaire de la kératine directement dans les fibres de cheveux humains. Il présente une grande spécificité moléculaire, détecter les interactions chimiques entre les molécules et peut fournir des informations moléculaires à différents niveaux de profondeur du cortex et de la cuticule. MÉTHODES Afin d’évaluer le potentiel de la spectroscopie Raman confocale pour tester l'efficacité des ingrédients cosmétiques sur la structure de la kératine, nous avons entrepris une étude pilote sur l'efficacité d'un shampooing lissant sur cheveux naturels, en analysant les marqueurs spectraux de l'hélice α et du feuillet β dans la bande Amide I et les marqueurs spectraux spécifiques au contenu en sulfure‐cystine. RÉSULTATS Nous avons confirmé qu'un actif s'avérant efficace sur un gold standard diminue la conformation de la kératine en hélice α et favorise la conformation de la kératine en feuillet β dans les fibres des cheveux. Nous avons également montré que le traitement avec l'actif efficace diminue l'intensité des bandes de cystéine réticulant sous forme de ponts disulfures covalents (S – S à 510 cm‐1). Ces données confirment que l'actif efficace agit également sur la structure tertiaire de la kératine. CONCLUSION À partir de ces expériences, nous avons conclu que l'actif efficace a un effet lissant sur les fibres du cheveu humain en agissant sur la conformation hélice α et feuillet β de la kératine et sur la structure tertiaire de la kératine. Sur la base de ces résultats, la spectroscopie confocale Raman peut être considérée comme une technique puissante pour étudier l'influence des ingrédients cosmétiques sur la structure de la kératine dans les fibres de cheveux. De plus, cette technique analytique a l'avantage d’être non destructive et ne nécessite pas de marquage; de plus, elle ne nécessite pas d'extraction ou de purification des échantillons et peut être appliquée en routine dans les laboratoires de cosmétiques. Confocal Raman spectroscopy can be considered as a powerful technique for investigating the influence of hair cosmetic ingredients on keratin structure in human hair fibres.